Bootstrap analysis for dissolution similarity factor f2 - bringing confidence for borderline results – a case study - Tina Achkoska; Marijana Bozhinovska; Angela Arnaudova; Packa Antovska; Anastasova, Liljana; Petkovska, Rumenka (Macedonian Pharmaceutical Association in cooperation with Ss. Cyril and Methodius University in Skopje, Faculty of Pharmacy., 2022)
In vitro dissolution testing is one of the most important tools for characterizing the performance of oral solid dosage forms. In order to demonstrate similarity between test and reference product, comparative dissolution profiles are performed. Selection of a suitable method for comparison of the dissolution profile of the reference product and the test product is of great importance especially in the case of biowaivers when similarity assessment is based on the in vitro data only. Various approaches have been developed for the comparison of dissolution profiles, however the usage of the f2 similarity factor is widely accepted due to its simplicity. When the conditions for using f2 similarity factor are not fulfilled due to high variable dissolution profiles, f2 bootstrap method is then recommended. The focus of this study is to see whether it is benefitial f2 bootstrap analysis to replace the usage of simple f2 for comparison of dissolution profiles that fulfill the prerequisites for using the f2 method in cases when borderline f2 results are obtained.
Keywords: Bootstrap analysis, comparative dissolution profiles, similarity factor f2